Increasing Foreign Language Proficiency and Critical Thinking: Based on Bloom’s Taxonomy - Shamsiddin qizi, Shakhriyorova Maftuna (Journal of Innovation in Education and Social Research, 2025)
This article examines the integration of task-based activities with Bloom's Taxonomy of Educational Objectives (Bloom's Taxonomy) in the context of English as a Foreign Language (EFL). Task-based learning is recognized for its ability to increase student motivation, stimulate critical thinking, and promote learning. By incorporating structure and tangible learning outcomes, even simple tasks can be elevated to create greater academic rigor for students. Educational taxonomies such as Bloom's taxonomy play a critical role in defining and differentiating the cognitive skills required to perform learning activities based on their complexity. Applying the taxonomy to tasks and curriculum provides a framework and establishes clear learning objectives. The purpose of the article is to demonstrate the use of Bloom's Taxonomy to provide structure and pedagogical skills to an English language task.